Peran Remaja Masjid Dalam Meningkatkan Dakwah di Masjid An-Nuur Kelurahan Damai Kecamatan Binjai Utara - Arlina Arlina; Mona Febrica Silva; Nurhasanah Sipahutar; Halimatussakdiah Harahap; Novia Fehbrina; Maria Ulfa Lubis; Putri Suci Ramadhani (STIT Sirojul Falah Bogor, 2023)
This study seeks to find out how the role of youth at the An-Nur mosque in the progress of da'wah. The research method is based on data sources, included in field research, and in terms of data characteristics, it is included in qualitative research and based on the discussion, it is included in descriptive research using a qualitative descriptive approach. Data was collected by observation, interview and documentation methods. Data analysis was carried out starting from data reduction, data presentation and drawing conclusions. The results of the study show that the existence of mosque youth has a very important function and role in its own community. In carrying out its role, the activities carried out by mosque youth in the Damai Village do not only focus on youth, but also on the mosque sector to expand the range of activities and services in achieving the prosperity of the mosque they aspire to. The existence of RM in prospering the mosque, namely by holding congregational prayers at the mosque, and commemorating holidays at the mosque, the impact of this RM from the management and active members themselves also shows to the community that their organization is a positive organization. Until now, the community is also very enthusiastic in supporting this youth mosque organization, and this also has a positive impact on members, namely, making many new members. Keywords: The Role of Youth in the Mosque, the Progress of Da’wah